Kinerja Manajemen Teaching Factory pada Program Keahlian Agribisnis Ternak di SMKN 1 Plosoklaten Kabupaten Kediri - Khusna, Nidaul; Sumarji, Sumarji; Daroini, Ahsin (Manajemen Agribisnis: Jurnal Agribisnis, 2026)
This study aims to analyze the implementation of the Teaching Factory (TeFa) at SMKN 1 Plosoklaten, specifically in the Livestock Agribusiness expertise program, and to identify factors influencing its performance and its impact on graduates. This study used a qualitative approach, with data collection techniques through observation, interviews, and documentation. The results indicate that the TeFa process at SMKN 1 Plosoklaten's Livestock Agribusiness has generally adopted industry standards through the POAC (Planning, Organizing, Actuating, Controlling) management function. The planning aspect has been synchronized with the industry and the National Standards for National Education (SKKNI), although the sheep unit does not yet have a formal learning plan. During the implementation phase, students are involved as pen operators through a 24-hour shift system for laying hens, broilers, cattle, and sheep. However, challenges were identified in the actuation aspect, such as low student discipline, varying motivations, and technical constraints such as damaged facilities and livestock shortages that disrupted the continuity of learning. Internal factors supporting the success of TeFa include adequate infrastructure (closed houses and colonies) and teacher resources, the majority of whom have competency certification. Externally, strong support comes from industry partners (PT Ceomas, UD Wahyu Jaya, and KUD Ngancar) in the form of production inputs, technical assistance, and product and graduate absorption. The implementation of TeFa has been shown to have a positive impact on improving students' technical competencies (hard skills) in line with industry standards. However, this has not been directly proportional to graduates' employment in the livestock sector, which is influenced by soft skills, work ethic, and students' career perceptions of the agribusiness sector. This study recommends strengthening the internalization of industrial work culture and utilizing technology (such as IoT) to increase operational effectiveness and enhance the attractiveness of learning for students.